2021
DOI: 10.32038/ltrq.2021.22.03
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Online Instruction amidst COVID-19 in Bangladesh: Barriers and Coping Strategies

Abstract: With the sudden onset of the COVID-19 pandemic and disruption of the education systems worldwide, private universities in Bangladesh transitioned to online classes to ensure continuity of education. Therefore, it was important to investigate the private university teachers’ and students’ perceptions regarding various dimensions of accessing online instruction and coping strategies used by teachers. A mixed-methods approach was used to collect data from 208 teachers and 674 students through questionnaires and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Khan et al [ 54 ] reported that high costs of the Internet and data affected lecture attendance. Interestingly, there was a discrepancy in the perceptions of the effectiveness of online education in the study (faculty thought it was effective while the students did not).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al [ 54 ] reported that high costs of the Internet and data affected lecture attendance. Interestingly, there was a discrepancy in the perceptions of the effectiveness of online education in the study (faculty thought it was effective while the students did not).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is crucial in emergency situations and in times after a pandemic, as there is a possibility that some features of online distance education will remain in the future, which is also pointed out by Aladrović Slovaček and Matković [ 56 ], who suggest professional training for teachers. In addition, Khan et al [ 54 ] mention a training proposal for students as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sudden emergence of COVID-19 pandemic disrupted the higher education system across the world where online learning has become vital, and universities are well aware of its significance during this pandemic (Khan et al, 2021). Various scholars have discussed the practical and theoretical issues related to ELLO.…”
Section: Research Frameworkmentioning
confidence: 99%
“…It works as a tool for the teaching-learning process to maintain social distance standards of procedures to curb this pandemic and limit its spread (Adedoyin and Soykan, 2020;Alrefaie et al, 2020). For this purpose, higher education institutions shifted their teaching practices to a blended learning model (Khan et al, 2021). It was important to know how self-concept, self-imagination, and self-efficacy influence ELLO among students through this model in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, Policymakers and administrators started to consider the online teaching-learning method to keep education going. In May 2020, the Ministry of Education (MoE) and University Grants Commission (UGC) permitted the universities to start online teaching learning and assessment (Khan, et al, 2021). The teaching methods were modified in online classrooms and the traditional paper-based assessments were replaced by the dig methods.…”
Section: Introductionmentioning
confidence: 99%